THEORETICAL AND PRACTICAL UNIVERSALITY OF MEMORY AND OBLIVION CATEGORIES IN LITERATURE - Valerii Bren (Lìteraturnij Proces: Metodologìâ, Ìmena, Tendencìï)
This research is devoted to the concepts of memory and oblivion in terms of the universality of these categories for literature, and their interdisciplinary in history, culturology, and sociology. The theoretical basis for analysis in the artistic text is shown on the example of Ukrainian and foreign researchers, specified and illustrated manifestations in the Ukrainian novels by Y. Andrukhovych, O. Zabuzhko, S. Zhadan, O. Irvanetz, etc. Literature is the centre of individual and national cultural memory and a means of creating of it. However, it becomes a platform for social discourse of memory, as well as the preservation of individual memory as a genetic key in the text. Consequently, modern literary studies require a well-balanced approach and analysis of the ways, means, methods, and forms of its functioning in contemporary art. Such approach will enable an understanding of the past experience, as well as assessments of contemporary imprints of events in the future, on a qualitatively new level.